The Effect of English as a Second Foreign Language On Learning Italian as a Third Foreign Language: A learner corpus-based research in written speech - FLOROU, KATERINA (International Journal of Language and Literary Studies, 2024)
In certain educational contexts, the study of learner corpora yields intriguing and valuable insights. This paper aims to examine and analyze the interference of English, learned as a foreign language, on the acquisition of Italian. To this end, we investigated a corpus of written productions by Greek students learning Italian as their first foreign language and a corpus of written productions by Greek students learning Italian as their second foreign language. Research on corpora has demonstrated its ability to provide both qualitative and quantitative insights into the interference effects of second language acquisition on third language learning. Our findings indicate notable patterns in the use of functional words; specifically, there is an underuse of articles and an overuse of personal pronouns, attributable to the structural differences between English and Italian. Conversely, students learning Italian as a third language displayed greater accuracy in their use of content words.